Taxonomic revision of Paraustrosimulium Wygodzinsky & Coscarón: reassignment of Austrosimulium colboi and description of P. obcidens n. sp. from Western Australia - Craig, Douglas A.; Moulton, John K.; Currie, Douglas C. (Zootaxa, 2017)
The hitherto monotypic South American genus Paraustrosimulium Wygodzinsky & Coscarón is revised to accommodate two Australian species: Austrosimulium colboi Davies & Györkös and Paraustrosimulium obcidens n. sp. The generic diagnosis is updated and the eastern Australian species Paraustrosimulium colboi (Davies & Györkös) n. stat. is re-described, including the male for the first time. The Western, Australian sister species of P. colbo, namely P. obcidens Craig, Moulton Currie n. sp. is also fully described. The relationship of Paraustrosimulium to other simuliid genera is discussed, as are aspects of historical biogeography.